Impact of International Remittance on Poverty Reduction in South West Ethiopia: Evidence From Jimma Zone (Global Journal of Management and Business Research, 2016)
This paper analyzes the impact of international remittances on poverty reduction in the Jimma zone of Ethiopia. The household surveyed data collected from 371 household heads in the year 2014 was used. The binary logistic model was applied to find out the impact of international remittances and other control variables on poverty status of households in the area under consideration. The result reveals that the poverty status of households negatively related with the inflow of international remittances. This implies that the household who receive remittances are less likely to be poor. In addition to this, family size, total land holding, amount of livestock owned, and distance from the nearest market were also significantly determine the poverty status. Finally, the study suggests the government should develop policies that encourage the inflow of remittances; such as providing better and relatively cheap means of transferring remittance, and developing an appropriate regulatory framework and monitoring mechanism of flow of remittances.
Keywords: impact; remittances; poverty reduction